2021
DOI: 10.1002/dc.24843
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Bethesda system for reporting thyroid cytopathology for classification of thyroid nodules: A clinical and cytopathological characteristics in Bhutanese population

Abstract: Introduction:The existence of baseline data on the spectrum of thyroid nodules in Bhutanese patients is unknown. Fine-needle aspiration cytology (FNAC) is regarded as the gold standard diagnostic test for pre-op assessment of thyroid lesions. Materials and Methods:We conducted a retrospective study, involving 765 patients who underwent FNAC of the thyroid gland, at Jigme Dorji Wangchuck National Referral Hospital, Thimphu, between January-2018 to December-2020. We aimed to assess the cytomorphological spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(58 reference statements)
2
1
0
Order By: Relevance
“…The Findings were comparable to the study done by Choden et al [6] In the present study, categorization of thyroid lesions based on the Bethesda system showed category 1 lesions-5.5%, category II lesions-85%, category III -2.5%, category III-3.5%, category IV-1%, Category V-4% and category VI-6%. These findings are comparable to the information gathered from earlier investigations done by Kanukuntla et al 15 and Swati et al There were three discordant cases in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The Findings were comparable to the study done by Choden et al [6] In the present study, categorization of thyroid lesions based on the Bethesda system showed category 1 lesions-5.5%, category II lesions-85%, category III -2.5%, category III-3.5%, category IV-1%, Category V-4% and category VI-6%. These findings are comparable to the information gathered from earlier investigations done by Kanukuntla et al 15 and Swati et al There were three discordant cases in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Five to six groups of well-preserved follicular cells, each having ten or more cells, should be present in an acceptable thyroid cytological smear. 2 This study showed an adequacy rate of 94.5%, which is found to be comparable with the studies done by Choden et al 6 and Nandedkar et al 2,6 In the present study, 87.57 % were female and 12.43% were male patients with a male-to-female ratio of 1:7. These results were comparable with Handa et al The cyto-histopathological correlation done on 33 patients showed high specificity in identifying malignant lesions, high negative predictive value, positive predictive value, and diagnostic accuracy, and a relatively low sensitivity as compared to previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Thyroid cytology classification systems play a crucial role in the accurate diagnosis and management of thyroid nodules, thereby influencing patient care outcomes [5,6]. In this study, a comparative analysis is conducted for five widely used classification systems: TBS, FRCPath, Australian, Japanese, and Italian systems, within the context of the Indian health-care system.…”
Section: Discussionmentioning
confidence: 99%